Lesson Learned from the Effect of Traffic Calming in a Downtown District of Szczecin, Poland for Congested Urban Center - Solowczuk, Alicja; Majer, Stanislaw (Science and Technology - Recent Updates and Future Prospects Vol. 2, 2024)
There has been a lot of research to overcome traffic jams, but the application of traffic calming has been very important since the past in Europe and the USA. The aim of this research is to carry out physical quantification based on impact analysis within the urban centre. Three street sections starting and ending with different intersection types were chosen to examine the synergy of the applied traffic calming measures. The numbers and speeds of vehicles were measured in three day-long continuous surveys. As it was expected, the amount of speed reduction depended on the hourly traffic volume on a one-way street and various other traffic engineering aspects. The obtained results may be used to modify the existing speed profile models and can guide traffic engineers in choosing the most effective traffic calming measures. In the near future, i.e., after the completion of the upgrading of all the streets in the analysed block, the authors plan to repeat the traffic volume and speed reduction measurements with the purpose of supplementing the existing zone 30 km/h speed profiles, if appropriate and required.